THE RELATIONSHIP BETWEEN FORMULA FEEDING AND LACK NUTRITION IN BATITA CHILDREN IN THE WORKING AREA OF HULONTHALANGI PUSKESMAS - bella ramadhani masitta (LPPM Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine the relationship between giving formula milk and the incidence of malnutrition in toddlers in the working area of the Hulonthalangi Health Center. Presentation of unclean formula milk can make babies susceptible to infection which results in less than optimal absorption of nutrients. The formulation of the problem in this study is whether there is a relationship between giving fomula milk and the incidence of Malnutrition in toddlers in the working area of the Hulonthalangi Health Center. This research uses quantitative research methods. The population in this study were 200 children aged 1-3 years (Batita). In this study, the samples taken were 35 toddlers using the solvine formula. The type of data used is primary data sourced from questionnaires. The data analysis technique used in this study was a descriptive analysis method which was carried out by means of descriptive statistics that describe or describe the data that has been collected by making generalizations of the research results using the chi-square test p = <0.05. The results of this study showed that there were 30 toddlers (85.7%) consuming formula milk and 5 toddlers (14.2) consuming breast milk, there were 6 toddlers (17.14%) experiencing malnutrition status and 19 toddlers (54 .28%) had normal nutritional status, and from the results of the Pearson chi-square test it was found that the result was 0.272 greater than p value = 0.05 which means that Ha is rejected and H0 is accepted so that it means that there is no relationship between giving formula milk and the incidence of malnutrition in toddlers in the working area of the Hulonthalangi Health Center in 2022.